2019
DOI: 10.1051/matecconf/201925303004
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Long-term Ageing on the Microstructure of Sanicro 25 Steel

Abstract: Sanicro 25 (22Cr25NiWCoCu) is a newly developed austenitic stainless steel used in the boiler pressure superheaters and reheaters with ultra-supercritical high-efficient parameters. The paper presents the results of microstructure testing and secondary phase separation processes after 20,000 h ageing at 700 and 750 °C. In the initial stage of ageing, the precipitation of numerous very small M23C6 chromium carbides and Laves phase were observed. The long-term ageing related to temperature revealed the existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…At the level of scientific research, an attention has been paid to the assessment of the metallurgical behavior of the stainless steels, including their aging behavior [5][6][7][8][9]. At hightemperatures and for prolonged holding times, several studies demonstrated that the microstructure of the austenitic stainless steels undergoes changes as the increase of the grain size and the decrease in the area of grain boundaries per unit volume [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…At the level of scientific research, an attention has been paid to the assessment of the metallurgical behavior of the stainless steels, including their aging behavior [5][6][7][8][9]. At hightemperatures and for prolonged holding times, several studies demonstrated that the microstructure of the austenitic stainless steels undergoes changes as the increase of the grain size and the decrease in the area of grain boundaries per unit volume [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%